»Skolefrihed«. Eckhard Bodenstein: Skolefrihed in Dänemark - Studien zur Entstehung eines schulpolitischen Prinzips. Mit dänischer Zusammenfassung - Nielsen, Vilhelm (Grundtvig-Studier, 1984)
Freedom of Education in Denmark - Studies in the Origin of a Principle of Educational Policy. Tønder 1962 (photocopy), by Eckhard Bodenstein Reviewed by Vilhelm Nielsen The author of this book is a lecturer at the Educational College in Flensburg, and he considers how it came about that Denmark has a law on “ compulsory education” and not “ compulsory schooling” . None of the countries with which Denmark is traditionally compared have such clear laws on the subject. That this has something to do with Grundtvig and the grundtvigian movement is generally recognised; but Bodenstein sets about deflating this “myth” or “ legend” through a scholarly examination of the facts. The main result is that it is neither Grundtvig nor the grundtvigians but instead J. N. Madvig - “the Latin professor” - who is the chief architect of the formulation and passing of the bill of May 2nd 1855, “the first free school law” , as it is called. Madvig was not a grundtvigian but a conservative-liberal. He wanted to make the 1849 constitution work, and he was a sincere supporter of the principles and ideas encoded in it, including the rights of parents against the state on the question of their children’s upbringing and education. He mastered the art of politics much better than the grundtvigians and was able to draft a bill that could be passed by both the lower and the upper chambers. In 1850-55 nobody in Denmark had much parliamentary experience or training, the political groupings were very loose, and the main interest was centred on the war and foreign relations. The passage of the school bill may seem faltering and confused; but it is here that Madvig’s clarity and consistency come into their own. For an understanding of his importance for the passing of the law it is now impossible to ignore Bodenstein’s conclusions. Another question, however, is whether this law is in fact of such crucial significance. Is it really a “ free school law” , and is it here that the distinction between “ compulsory education” and “ compulsory schooling” is drawn? Points against this are 1) It does not abolish the first school bill from 1814, 2) It is concerned with home education, not free schools or private schools, 3) the subsequent control of home education entails in practice just as many problems as the previous authorization had sought to achieve, 4) the law omits to mention what has persuaded people, especially on Funen, to make use of the opportunities for establishing free schools both before and after 1855. But here Madvig’s principles and conceptual clarity are not enough. And this goes to some extent for Bodenstein as well. The driving force behind the development is not abstract principles. A parliamentary debate and a law and its administration over a number of years may possibly crystallize into principles and concepts, but the question is whether one does not thereby follow a false scent and miss the essential. In his relentless demand for “conceptual analysis” Bodenstein lacks “distance” to his own concepts and to the reforming pædagogics of our century. The reviewer is not a legal expert but an educationist, and this book deals with one particular legal text. As a civil servant in the Ministry of Education he has acquired much respect for the knowledge of legal experts and would have preferred a jurist to review the book. With this reservation, however, the following can be established: 1. The 1814 bill aimed at compulsory schooling but also opened up the possibility of home education. There was no intention of destroying or hindering the activities of private tutors out in the country engaged by persons whofor the most part were prosperous and well-educated. The law thus contained a “ subsidiary principle” , (alternative principle). 2. Paragraph 90 of the 1849 constitution turns this on its head. According to the wording, compulsory schooling becomes subsidiary to the parents’ home education. Madvig feels himself duty-bound to this principle and builds on it. Compulsory education is thereby introduced in principle instead of compulsory schooling. 3. The bill of May 2nd 1855 can be regarded as a kind of clarifying measure; but it does not repeal the 1814 law, it merely sets up a subsequent supervision instead of a preceding approval of home education. There is much evidence to support Grundtvig’s claim that it could all have been managed administratively. A new bill was unnecessary. 4. With some experience as a private tutor to the children of several different families Christen Kold founded a free school in 1852 at Dalby on Funen with 16-20 children, rising to 60-65 in 1855. Preparations for the founding of other schools on Funen were also well under way. On the basis of these “layman’s considerations” Vilhelm Nielsen questions whether the bill of May 2nd 1855 was of such great importance for the problem of compulsory education vis-a-vis compulsory schooling as to be able to defend it as the first free school law. One must especially protest against Bodenstein’s calling the law “ creative” in contrast to most of the other laws, which he calls “ registering” . The free school supporters did not think in principles and concepts but in individual children and peasants in difficulties. Economic motives play a major role in the parliamentary debate in various “petitions” from outside; but Vilhelm Nielsen considers it neither reasonable nor well-founded to regard Grundtvig or the “grundtvigians” ’ argument for the educational advantages of the move as an ideological superstructure over what was in fact an economic demand. Grundtvig really did believe that everyone, including the gifted, should learn to use their hands, not for economic, but for educational reasons (cf. Open Letter to My Children and To My Two Sons). Bodenstein’s mistake at this point is tofail to distinguish between the grundtvigians and the friends of the peasants. The reviewer finds it strange that Bodenstein does not refer to Andreas Austlid’s Christen Kold (3rd ed. 1951) when he makes use of an unpublished biography of Hass, who was linked with Kold. Bodenstein may be right in seeing the literature on the free schools as uncritical and legendary: at a scholarly level it is a neglected area. But then nor is a point-by-point analysis of a parliamentary debate particularly comprehensive. Apart from his parliamentary speeches the only Grundtvig texts which appear in the bibliography are Grundtvig1's Educational World in Texts and Extracts by K. E. Bugge. Without insight and empathy a modern scholar can hardly understand much of Grundtvig. But according to Bodenstein Grundtvig research in the last few decades has lacked “the critical, spiritual distance to Grundtvig and Kold” . However, it is the reviewer’s impression that precious few Grundtvig scholars would call themselves grundtvigians. The poetic and the mysterious is a more powerful magnet than the transparent. But it is to be hoped that the author will one day discover that Grundtvig is not an antiintellectual, even though he places imagination and feeling above reason. But everything aims at a rational clarification in the end.